A Tactical Urbanism and Economic Inclusivity: Evaluating the Impact of Spacena Project in a Marginalized Urban Area - Alhadyan, Shahed; AlRahahleh, Mohammad; Khwaileh, Mysaa (Alanya Üniversitesi, 2024)
Addressing economic and social inequalities in urban settings, particularly those that affect marginalized groups, is becoming more challenging. In less privileged urban areas, women entrepreneurs face restricted opportunities, specifically in limited retail activities in urban spaces. This study examines the effects of implementing a tactical urbanism solution known as